Dampak Relokasi Pasar Terhadap Tingkat Kunjungan Dan Pertumbuhan Pedagang Bagi Pedagang Keripik Belut Di Pasar Godean - Susilawati , Rini; Pratomo, Arief Budi; Purdwiastuti, Maria Magdalena (Jurnal Solusi, 2018)
he relocation of trading places always has an impact that is sometimes very positive, but it is not uncommon to also often occur that the relocation of trading places sometimes has a negative impact. There are many examples of relocation that have a positive impact on Yogyakarta, such as the Animal Market Relocation from Ngasem Market and Kuncen Market to the Animal and Plant Markets in Yogyakarta (PASTY), the results are relatively good and positive. Then another successful example is the relocation of the Klithikan market (used goods) from the entire Mangkubumi road to the new location in the former Kuncen Market. But there are also those who relocate to a new place the impact is just the opposite. One of the less successful relocations is the relocation of eel traders from this Godean Market. To the Culinary Center of Godean eel. The results of this study found several factors that led to the lack of success of relocation at the Godean Eel Culinary Center. Some of the indicators used in this study are in terms of decreasing the level of visits and the decreasing number of eel traders occupying the relocation site.